WNT Signaling Is a Key Player in Alzheimer's Disease - Inestrosa, Nibaldo C.; Tapia-Rojas, Cheril; Cerpa, Waldo; Cisternas, Pedro; Zolezzi Moraga, Juan Manuel (My University, 2021)
The cellular processes regulated by WNT signaling have been mainly studied during embryonic development and cancer. In the last two decades, the role of WNT in the adult central nervous system has been the focus of interest in our laboratory. In this chapter, we will be summarized beta-catenin-dependent and -independent WNT pathways, then we will be revised WNT signaling function at the pre- and post-synaptic level. Concerning Alzheimer's disease (AD) initially, we found that WNT/beta-catenin signaling activation exerts a neuroprotective mechanism against the amyloid beta (A beta) peptide toxicity. Later, we found that WNT/beta-catenin participates in Tau phosphorylation and in learning and memory. In the last years, we demonstrated that WNT/beta-catenin signaling is instrumental in the amyloid precursor protein (APP) processing and that WNT/beta-catenin dysfunction results in A beta production and aggregation. We highlight the importance of WNT/beta-catenin signaling dysfunction in the onset of AD and propose that the loss of WNT/beta-catenin signaling is a triggering factor of AD. The WNT pathway is therefore positioned as a therapeutic target for AD and could be a valid concept for improving AD therapy. We think that metabolism and inflammation will be relevant when defining future research in the context of WNT signaling and the neurodegeneration associated with AD.
Keywords: alzheimer's disease; amyloid-beta; glucose metabolism; inflammation; synaptic dysfunction; tau phosphorylation; wnt signaling; wnt/beta-catenin